Melioidosis Presenting as Chronic Pneumonia With Soft Tissue Abscess in a Diabetic Patient Initially Treated for Tuberculosis: A Case Report From Vietnam - Huy Quang Nguyen; Tra Thu Doan; Thanh Van Do; Cuong Duy Do; Vuong Minh Nong; Co Xuan Dao; Giap Van Vu (Respirology Case Reports, 2025)
ABSTRACT A 46‐year‐old diabetic Vietnamese engineer presented with a 2‐month fever and left foot swelling. Chest imaging showed bilateral nodules with right apical cavitation, prompting empirical anti‐tuberculosis therapy. Despite positive Xpert MTB/RIF and 1 month of treatment, his condition worsened. Bronchoscopy culture isolated Burkholderia pseudomallei. Treatment with ceftazidime and trimethoprim‐sulfamethoxazole led to complete recovery. Negative MGIT culture excluded tuberculosis co‐infection. This case highlights the diagnostic challenge when melioidosis mimics tuberculosis in endemic regions, particularly in diabetic patients. Positive molecular tuberculosis tests may reflect the previous infection, emphasising the need for culture confirmation and clinical correlation.